National security of Ukraine in the context of legal regulation in the sphere of ecological problems - Логвиненко, Олена Іванівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
The aim of the paper is the development of the normative-legal basis of the competence of the Ministry of Ecology and Natural Resources of Ukraine in the sphere of ecological security and the formulation of recommendations for its improvement. Statement of the Problem and its Relevance. Today the level of environmental risk depends upon the effects of human activities. A man begins to understand that the nature should be perceived in several aspects: as a mighty force and as a fragile organism that can be destroyed by careless actions. From the end of last century, realizing that the state of the environment depends on human activities, the world community began to show greater interest in its protection, the development of countries and regions for preserving the environment for future generations. The aim of the paper is the development of the normative-legal basis of the competence of the Ministry of Ecology and Natural Resources of Ukraine in the sphere of ecological security and the formulation of recommendations for its improvement. Analysis of Studies and Publications. Several issues related to brought up questions are reflected in the writings of scholars V.I. Andreytsev, G.I. Baliuk, Y.S. Shemshuchenko, Y.M. Todiko, S.B. Gavrish, O.S. Zarzhitsky, A.B. Kachinsky, B.G. Rozovsky, V.I. Kurilo, V.A. Lipkan, V.L. Muntian, L.O. Bondar, V.V. Petrov etc. Given the current state of the environment and the lack of an ordered system of legal acts and the common concept of environmental security, the state in accordance with international standards has defined as one of the strategic objectives the reforming in the field of environmental security, for the ensurement of the harmonious development of man and preservation of the environment for future generations. In Ukraine, the issues of environmental security are engaged in a number of state agencies, among which a prominent place belongs to the Ministry of Ecology and Natural Resources of Ukraine. According to the analyzed proposals of the scientists who believe that there is a reform of the central public authorities, including the sphere of environmental safety, it would be useful to distinguish these authorities on the basis of the resource approach and differentiation of powers of disposal of natural objects, control and inspection powers. For such reason, the structure of the central public authorities would consist of two departments in the complete absence of signs of affiliation with each other. It quite regards central government authorities empowered in the field of environmental security. Thus, according to the sphere covered by the competence of the central authorities and on the basis of resource approach and differentiation of powers, it would be logical to delimit the Ministry of Ecology and Natural Resources in two equivalent authorities of the central government. In the list of functions of the central authority exercising powers in the sphere of preservation and protection, it is necessary to fix: the control of inspection, conciliation (in terms of approval limits of the use of natural objects at the level of the state and administrative-territorial units), expert, inspection (verifying the compliance with environmental legislation the enterprises, institutions and organizations irrespective of forms of ownership), information (information about the state of the environment and the results of their activities). The central authority in the field of scientific support and use of objects of the environment (resource control) will carry out scientific-organizational, information and training (information about the state of the natural environment and carrying out training activities) and environmental monitoring functions. In our opinion, it should be improved firstly the regulatory support in the field of environmental safety in accordance with modern realities and created an integral and perfect mechanism of administrative-legal regulation in Ukraine with regard to responsibility both individuals and business entities.